Reuse Techniques of Residential Stock in Urban fabric of the Old Cities Analytical study of international experiences in sustainability of historic centers - AlAllaf, Emad H.; AlHayali, Mohammed M. (Sulaimani Journal for Engineering Sciences, 2019)
Traditional residential buildings within the urban fabric of old cities are one of the most densely populated housing patterns in the Arab countries, which represent an important part that provides shelter for a large group of residents with its unique characteristics. Due to the factors of decay and deterioration over time, many of these buildings become unsuitable for occupancy, demand a rapid intervention to revitalize and utilize. Globally, in many successful experiences, many of these sectors have been re-employed and rehabilitated by either a maintenance-based methodology as part of the local heritage to be maintained or by prolonging its functional age by exploiting a new use to serve the local community. In the Arab world, the heritage cities have been suffering from many problems, the most important of which is the negative impact of urban development on the residential environment, because it has not been able to meet the current requirements, making it an unsuitable environment for modern housing, causing a change in its accommodation functional structure, and to convert to other employments, and with its indigenous inhabitants abandoned, threatened the social and historical value of its urban fabric. The research aims at presenting general guidelines that can be adopted in the rehabilitation of traditional residential buildings by examining the possibility of accepting the characteristics of these buildings to the contemporary requirements without harming their heritage value, by reviewing and analyzing a number of successful international experiences in the rehabilitation field of old cities, and extracting a set of principal guidelines for the purpose of employment in the sustainability of traditional housing stocks.
Keywords: Architectural Conservation; Reconstruction; Heritage Residential Buildings; Old Mosul